“MODERN PSYCHOLOGY” - CURRENT BOARD OF PUBLIC PRESENTATION OF SCIENTIFIC ACHIEVEMENTS - Avanesyan, H.M . (Modern Psychology, 2018)
The article is devoted to the principles of design and application of criteria of scientific publications in the field of modern psychology. Particularly, the author discusses the problems of theoretical bases of empirical studies, the use of methodological principles, semantic and terminological problems, and also the purpose and scientific-applied direction of the scientific bulletin "Modern Psychology".
Keywords: scientific psychology; methodology; research; terminology; principles; problems